Walter B. Wriston and Citicorp/Citigroup notables at groundbreaking for Citicorp Center (Tufts Archival Research Center, 2008)
7.5 x 9.5. This date is approximate. Thomas Creamer (Citicorp/Citigroup), Walter B. Wriston (Citicorp/Citigroup), and Reverend Ralph E. Peterson (St. Peter's Church) at the groundbreaking for Citicorp Center. This image is copyrighted to Citigroup. The print and digital image were created from 'File2824' from the CD titled 'Walter B. Wriston Photographs - CD 3'.